â€œALADDINâ€ FROM ARABIAN NIGHTS TO DISNEY: THE CHANGE OF DISCOURSE AND IDEOLOGY - Rahayu, Mundi; Abdullah, Irwan; Udasmoro, Wening (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2015)
This study compares the folktale â€œThe Story of Aladdin and the Wonderful Lampâ€ from the Arabian Nights, and the animated film produced by Walt Disney Feature Animation under the title â€œAladdinâ€ (1992). The differences of those two stories in two different medias shows the shifts of ideology and discourse. The study applies Faircloughâ€™s Critical Discourse Analysis, by applying the three stages of analysis.Â The first level is micro level, on the language practice. In the second level, mezo level, discusses the discourse practice that covers the intertextuality of ideas, concept as the reference in delivering the ideas. In the third level, macro level, it interprets the social context ofÂ Â particular events, especially the social practice in exercising their power. The finding shows that the Disneyâ€™s Aladdin campaigns ideology that refers to the American values such as freedom and American heroism. Besides, the discourse of Arab barbarism is developed in line with the practice ofÂ Â stereotyping such as labeling the Arab people as barbaric, bad, silly and wicked as well as dangerous Arabs. These imply to the removals of the Islamic messages and values that exists in the original tales of Arabian Nights. The Disneyâ€™s Aladdin completely removes the Islamic messages and values, and changes them into â€˜American valuesâ€™.